Effects of brown algae extract to function of aorta endothelium cell in diabetic rats - Muhamad Firdaus; Made Astawan; Deddy Muchtadi; Tutik Wresdiyati; Sarwono Waspadji; Setyawati S. K. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Macro and microvascular disease are currently the principal causes of morbidity and mortality in diabetes mellitus patients. Loss of the modulatory role of the endothelium may be a critical and initiating factor in the development of diabetic vascular disease. Polyphenol is known behave protective active compound to function endothelium cell. Polyphenol that contained in brown algae was phlorotannin. The aim of the present study was to investigate the effects of S. echinocarpum extract on endothelial dysfunction in aorta of streptozotocin diabetic rats. This experiment was conducted by complete randomized design in 2 months old of male albino Sprague Dawley strain of rats, 125-150 grams body weight. The rats divided in fivegroups, each group consist of 6 rats. First group: normal which is given 1 mL of extract vehicle orally; second group: diabetic rats which is given 1 mL of extract vehicle orally; third group: diabetic rats which is treated extract 150 mg/kg BW dose orally; fourth group: diabetic rats which is treated extract 300 mg/kg BW dose orally; and fifth group: diabetic rats which is treated extract 450 mg/kg BW orally. Diabetic rats prepared by injection of 45 mg/kg streptozotocin intraperitoneally. Extract was given to diabetic rats during 90 days. The result showed that brown algae extract rearrange endothelium cell function of diabetic rats by increasing relaxation, releasing of EDRF and decreasing of MDA. Based on these observations, it was concluded that S. echinocarpum extract recovers the endothelial dysfunction associated with diabetes. This effect appears to be due to its antioxidant properties.Key words: diabetes, EDRF, endothelial dysfunction, MDA, S. Echinocarpum